VITAMIN D SUPPLEMENTATION AND COVID-19 OUTCOMES : A SYSTEMATIC REVIEW - Talilah, Stephanie (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
The COVID-19 infection is a pandemic that is still continuing strong and is marked by significant morbidity and fatality rates. It is imperative that clinical and biological predictors of severity and mortality associated with COVID-19 infection be identified as quickly as possible in order to make efficient use of the resources that are available. The development of efficient vaccinations and therapeutic compounds is currently the primary focus of research efforts; however, many industry professionals stress the need of enhancing one's immune system through a variety of nutritional approaches. A study investigation into the numerous treatment options available for COVID-19 infection has led them to lay an increased emphasis on the function of micronutrients as supplementary and supportive components of therapy regimens. According to a number of studies, higher levels of vitamin D in the body or taking vitamin D supplements is connected with a lower risk of dying. Those who took vitamin D supplements had a longer life expectancy, despite the fact that the levels of vitamin D in their bodies were not evaluated after receiving the supplementation in several of the trials.